2007
DOI: 10.1007/s10194-007-0396-5
|View full text |Cite
|
Sign up to set email alerts
|

Migraineurs with patent foramen ovale have larger right-to-left shunt despite similar atrial septal characteristics

Abstract: The objective of the study was to assess differences in proportion of large right-to-left shunt (RLS) and atrial septal characteristics between migraineurs and non-migraineurs referred for transcatheter closure of patent foramen ovale (PF0). This retrospective study took place in a large metropolitan medical centre. The patients were migraineurs with aura (n=52), migraineurs without aura (n=19) and non-migraineurs (n=149). RLS was evaluated before closure using bilateral power m-mode transcranial Doppler at re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
2

Year Published

2008
2008
2011
2011

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 39 publications
2
17
0
2
Order By: Relevance
“…People with migraine with aura were more likely to have a PFO than migraineurs without aura. A small study of 25 consecutive patients with migraine with aura revealed a prevalence of PFO in 88.7%, according to the contrast transcranial echocolour-coded sonography and 72% according to the transoesophageal echocardiography [82]. A Swedish retrospective study in patients referred to transcatheter closure of PFO showed that migraineurs had a higher proportion of large right-left-shunts at rest and strain than non-migraineurs [83].…”
Section: Patent Foramen Ovale In Migraineursmentioning
confidence: 97%
“…People with migraine with aura were more likely to have a PFO than migraineurs without aura. A small study of 25 consecutive patients with migraine with aura revealed a prevalence of PFO in 88.7%, according to the contrast transcranial echocolour-coded sonography and 72% according to the transoesophageal echocardiography [82]. A Swedish retrospective study in patients referred to transcatheter closure of PFO showed that migraineurs had a higher proportion of large right-left-shunts at rest and strain than non-migraineurs [83].…”
Section: Patent Foramen Ovale In Migraineursmentioning
confidence: 97%
“…Although ASDs are most often associated with left-to-right shunting of blood, right-to-left shunting may occur during Valsalva or other activities increasing right atrial pressures. Studies on the effects of ASD repair and the prevalence and outcome of migraine have not reported a significant benefit [24,25].…”
Section: Cardiac Comorbiditymentioning
confidence: 99%
“…The association is stronger between migraine with aura and PFO; the prevalence of PFO in patients with migraine with aura is higher (48%) compared to patients with migraine without aura (23%) and controls (20%) [65]. Also, patients with migraine tend to have greater right to left shunt in comparison to the normal population [68,69]. However, the association of PFO, migraine with aura and stroke is not conclusive.…”
Section: B1 Migrainementioning
confidence: 96%